Association Between Vitamin D and Hyperuricemia Among Adults in the United States - Zhang, Yi-Ying; Qiu, Hong-Bin; Tian, Jin-Wei (Frontiers in Nutrition, 2020)
Background: Serum uric acid can act as a risk factor for cardiovascular disease (CVD) and as antioxidant defense. Vitamin D deficiency can activate the parathyroid to induce the release of parathyroid hormone, which was thought to increase serum uric acid level, and low vitamin D status may also be associated with risk of CVD. No known studies have explored the association between serum 25(OH) D, vitamin D intake, and HU for the American population. Methods: We extracted 15,723 US adults aged 20–85 years from the National Health and Nutrition Examination Survey (NHANES) in 2007–2014. All dietary intakes were evaluated through 24-h dietary recalls. Multivariable logistic regression analysis was performed to examine the associations after adjustment for confounders. Results: Compared to the lowest quintile (Q1), for males, adjusted odds ratios (ORs) of HU in Q2 to Q4 of serum 25(OH) D levels were 0.78 (95% CI, 0.65–0.93), 0.97 (0.81–1.16), and 0.72 (0.60–0.88); ORs in Q2–Q5 of total vitamin D intake were 0.83 (0.69–0.98), 0.69 (0.58–0.83), 0.66 (0.55–0.79), and 0.59 (0.48–0.71), respectively. In females, OR was 0.80 (0.66–0.97) of serum 25(OH) D for Q3, and ORs in Q5 of total vitamin D intake were 0.80 (0.65–0.98). Conclusions: Our findings indicated that the serum 25(OH) D intakes of dietary vitamin D, supplemental vitamin D, and total vitamin D were inversely associated with HU in males. In females, a lower risk of HU with higher serum 25(OH) D, dietary vitamin D, and total vitamin D intake was found, but with no association between supplemental vitamin D intake and the risk of HU.